Analisis Dan Perancangan Ulang Antarmuka Pengguna Menggunakan Aspek Visual Design Dan Layout Design Pada Aplikasi Air Duasudara Mobile - Mozart Wowiling; Chriestie Montolalu; Stephano Ngangi (INTECH, 2026)
Digital transformation in public services requires mobile applications that provide not only functional services but also effective and user-friendly interfaces. The Air Duasudara Mobile application, developed by Perumda Air Minum Duasudara Kota Bitung, still faces several issues related to visual design and layout design, including low typography readability, unclear icons, confusing navigation, inconsistent interface elements, and ineffective information arrangement. This study aims to analyze these issues and redesign the user interface to improve usability and user experience. The research employed the Design Thinking method consisting of five stages: empathize, define, ideate, prototype, and testing. Data were collected through observations, interviews with PDAM staff and application users, and questionnaires. The redesign process resulted in a high-fidelity prototype developed using Figma with a more structured, consistent, and user-centered interface. The proposed design was evaluated through usability testing using Maze and user experience assessment using the User Experience Questionnaire (UEQ). The usability testing results involving 21 respondents showed high task completion rates across major features, while the UEQ evaluation achieved Excellent ratings in five dimensions and Good in one dimension. The findings indicate that the application of Design Thinking effectively improved the visual design and layout design of the Air Duasudara Mobile application, resulting in better usability and a more positive user experience.